PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Noormala Dewi, Syahrina (BISNIS, 2015)
The financial report is the information about the performance of thecompany and report to the stakeholders responsibility them. In generalthe financial report aims to provide financial information a company,both in time and in a certain period of both arranged all of a sudden inaccordance with the requirements of the companies and periodically.The analysis of the data using the double linier regression as describedpreviously obtained that the model developed in this research isworthy (fit) and successfully shows as a good model. The results ofthis study only gives the meaning of the variables the size of the boardof commissioners and leverage that is able to explain the broad socialdisclosure significantly strengthened